Multiline transfer and the dynamics of stellar winds - Abbott, D. C.; Lucy, L. B. (The Astrophysical journal, 1985)
A Monte Carlo technique for treating multiline transfer in stellar winds is described and tested. With a line list containing many thousands of transitions and with fairly realistic treatments of ionization, excitation, and line formation, the resulting code allows the dynamical effects of overlapping lines to be investigated quantitatively, as well as providing the means of directly synthesizing the complete spectrum of a star and its wind. As a direct result of this improved treatment of multiline transfer, the computed mass loss rate for Zeta Puppis is now found to agree with the observed rate. The synthesized spectrum of Zeta Puppis also agrees with observational data. These results confirm that line driving is the dominant acceleration mechanism in this star's wind.